Germination of Aechmea gamosepala seeds under various temperatures, substrates, and lighting conditions - Thiago Alberto Ortiz (Technology in Horticulture)
The use of native species from different ecosystems can contribute to increased environmental biodiversity. Despite the abundant plant genetic resources, there are few initiatives for the conservation, domestication, and sustainable use of these species. Therefore, this research aimed to evaluate the influence of temperatures, substrates, and lighting conditions on the germination of Aechmea gamosepala seeds. The experiment was conducted with bromeliad seeds (A. gamosepala Wittm.) using a completely randomized design with a 5 × 5 × 2 factorial scheme. The factors included five temperatures (15, 20, 25, 30, and 35 °C), five substrates (blotting paper, sand, vermiculite, coconut fiber, and charred rice husk), and two lighting conditions (presence and absence of light), with four replications. The analyzed variables were germination percentage (G), germination speed index (GSI), and mean germination time (MGT - days). The data were subjected to analysis of variance, and regression models were fitted for all variables when significant. It is recommended that A. gamosepala seed germination be conducted in the presence of light at a temperature of 25 or 30 °C, as these conditions favor the variables G, GSI, and MGT. The substrates of paper, sand, vermiculite, or coconut fiber are suitable for germination, whereas the carbonized rice husk substrate is not favorable for the initial development of this species.